Micropillar Compression of MoSi2 Single Crystals. Issue 1760 (13th January 2015) - Nakatsuka, Satoshi; Kishida, Kyosuke; Inui, Haruyuki
ABSTRACT: Deformation behavior of MoSi2 has been studied by micropillar compressions of single crystalline specimens prepared by focused ion beam (FIB) technique as a function of crystal orientation at room temperature. Activation of the {011}<100> and {01 $\overline 3$ }<331> slip systems were observed in the micropillars compressed along [ $\overline 1$ 10] and [0 15 1], respectively. The CRSS values for each slip system exhibit an approximate power law relationship with the edge length of micropillar. The {01 $\overline 3$ }<331> slip exhibit much stronger size-dependence than the {011}<100> slip system.